2011
DOI: 10.1016/j.jacc.2010.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Use of Intravenous Gamma Globulin and Corticosteroids in the Treatment of Maternal Autoantibody-Mediated Cardiomyopathy

Abstract: Treatment of maternal autoantibody-mediated fetal cardiomyopathy/endocardial fibroelastosis with IVIG and corticosteroids potentially improves the outcome of affected fetuses. Further studies are needed to determine the optimal dose and timing of IVIG administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 37 publications
0
80
1
4
Order By: Relevance
“…However, the effectiveness of these agents in the treatment of endocardial fibroelastosis is unknown [41]. In a retrospective study for the use of glucocorticoids and IVIG (both in utero and after birth), a potential survival benefit was observed in cases with cardiomyopathy/endocardial fibroelastosis based upon comparison to historical control data [86].…”
Section: Cardiac Diseasesmentioning
confidence: 99%
“…However, the effectiveness of these agents in the treatment of endocardial fibroelastosis is unknown [41]. In a retrospective study for the use of glucocorticoids and IVIG (both in utero and after birth), a potential survival benefit was observed in cases with cardiomyopathy/endocardial fibroelastosis based upon comparison to historical control data [86].…”
Section: Cardiac Diseasesmentioning
confidence: 99%
“…14 In a non-randomised multi-centre study of 20 foetuses exposed to maternal lupus antibodies 15 it was found that treatment with intravenous gamma globulin and steroids potentially improved the outcome for these children, with better than expected survival. However, a prospective study of 165 foetuses with exposure to anti-Ro/La antibody found that foetal atrioventricular prolongation did not predict progression to heart block, so management based on the strategy of identifying and treating foetal atrioventricular prolongation was questioned.…”
Section: Foetal Cardiologymentioning
confidence: 99%
“…With earlier detection of more subtle atrioventricular block in the context of maternal autoimmune mediated fetal heart disease, we have begun to better understand the clinical evolution of this disease, its association with other arrhythmias such as junctional ectopic and ventricular tachycardia, and sinus node dysfunction and more diffuse myocardial disease, and to explore strategies to improve the survival of affected fetuses [51][52][53][54][55][56].…”
Section: Fetal Arrhythmiasmentioning
confidence: 99%
“…Initial interest in earlier assessment stemmed from the advent of endovaginal transducers in the late 1980s which permit imaging in closer proximity to the fetus at less than 14 weeks of gestation through the maternal cervix [56][57][58]. Recognition that transabdominal imaging with high frequency transducers permits assessment of many pregnancies at earlier ages has also resulted in greater enthusiasm for early screening among pediatric cardiologists who have not been trained and/or are uncomfortable with transvaginal imaging [60][61][62].…”
Section: First Trimester Fetal Echocardiographymentioning
confidence: 99%
See 1 more Smart Citation